UPAYA MENINGKATKAN ASPEK NILAI AGAMA DAN MORAL MELALUI METODE BERCERITA ANAK USIA 5 – 6 TAHUN DI PAUD MADANI PARUNGPANJANG - Nurhayati Nurhayati; Puji Yulianti (Jurnal Anak Bangsa, 2023)
This study aims to improve aspects of religious and moral values ​​through the storytelling method in PAUD Madani Parungpanjang. The research method used is Classroom Action Research. The population used in this study was 15 students consisting of 4 boys and 11 girls. Data collection techniques in this study used interview, observation and documentation techniques. While the data analysis technique is carried out in a qualitative and quantitative descriptive manner. Based on observations, when research showed an increase in aspects of religious and moral values ​​through the storytelling method in PAUD Madani Parungpanjang, this was evidenced by the pre-cycle with an average of 53.6 if the percentage reached 13%, in cycle I with an average of 74 if the percentage reached 26% and in cycle II with an average of 89.6 if the percentage reaches 60%. This is evidenced by the increasing aspects of religious and moral values ​​through the question-and-answer method at PAUD Madani Parungpanjang